Health Provision in Tshitshi, Zimbabwe: A Focus on Sexual and Reproductive Health - Moyo, Samantha Zanele (Department of Sociology, 2022)
Political conflict in Zimbabwe led to a series of crises that has negatively affected the nation's socio-economic status for over a decade now. The public sector's ability to provide basic services has been affected by a dead economy: the scarcity of resources such as money, water, energy, food, and medical care has meant that a once-desirable system has become dysfunctional and is too incapacitated to meet the needs of the public. The population has been reduced to paupers and forced to adopt informal survival strategies to access services that in a functional economy would have been provided by the government. Little is known about how services that cannot be forfeited, in particular sexual and reproductive health (SRH) services, are accessed by the most severely disadvantaged segment of the population: people living in rural areas. This study explores how the economic crisis shapes Tshitshi women's access to and use of SRH services. Specifically, it maps out Tshitshi women's experiences in accessing SRH services, the coping mechanisms, and the non-biomedical alternatives within the socioeconomic deprivation they encounter. Data was collected in Tshitshi village located in Matabeleland South province of Zimbabwe using qualitative methods through focus group discussions and in-depth interviews. In analysing data, I used thematic analysis with the help of NVivo version 12 to identify and sort themes. The study adopted the transnational care framework which was informed by the findings of the research, where I identified transnational medical resources and care as the overarching theme. Findings show that Tshitshi women's access to and use of SRH services is mostly influenced by transnational care resources which is how they improvise and manage the healthcare genocide. To cope with the lack of biomedical services, Tshitshi women improvise and access non-biomedical services which present convenience in availability, affordability, and acceptability. The study results elicited recommending outsourcing of medical supplies as an acceptable measure provided the state can be trusted to commit to meeting the needs of the people in positive sustainable ways.